Rozwiązane

Rozwiąż równanie.

a) 3x + 7 = 2x + 1

b) x = 8 - 3x

c) 2x - 4 = 4x - 2

d) 7 - 2x = 5x + 28

e) 8x - 5 = 9x - 5

f) 6x + 2x - 10 = 3x + 5

g) x + 2x + 3x = 5 + 6 + 7

h) 4x - 1 + 5x = 6x + 1 - 7x

i) 0 = 4x - 4 + 5x - 5



DAM NAJ!!!​



Odpowiedź :

Odpowiedź:

a)3x-2x=1-7

x=-6

b)x+3x=8

4x=8/:4

x=2

c)2x-4x=-2+4

-2x=2/:(-2)

x=-1

d)-2x-5x=28-7

-7x=21/:(-7)

x=-3

e)8x-9x=-5+5

x=0

f) 6x+2x-3x=5+10

5x=15/:5

x=3

g) 6x=18/:6

x=3

h) 4x+5x-6x+7x=1-1

10x=0

x=0

i)-4x-5x=-5-4

-9x=-9/:(-9)

x=1

Szczegółowe wyjaśnienie: